2018
DOI: 10.3390/jof4040115
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Treatment of Mycoses in Pediatric Patients

Abstract: The main indications for antifungal drug administration in pediatrics are reviewed as well as an update of the data of antifungal agents and antifungal policies performed. Specifically, antifungal therapy in three main areas is updated as follows: a) Prophylaxis of premature neonates against invasive candidiasis; b) management of candidemia and meningoencephalitis in neonates; and c) prophylaxis, empiric therapy, and targeted antifungal therapy in children with primary or secondary immunodeficiencies. Fluconaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 142 publications
(197 reference statements)
0
26
0
Order By: Relevance
“…66 Drugs such as voriconazole and LAMB are used to treat infections caused by Aspergillus species, also other new drugs such as anidulafungin and isavuconazole are considered to be used widespreadly but this requires further studies. 54,67,68 For example, the results of a recent study showed that prophylaxis with isavuconazole is not effective in preventing invasive Aspergillus infections, and further studies are needed to use this drug widely. 52 Furthermore, drug resistance is a critical issue in Aspergillus species.…”
Section: Aspergillosismentioning
confidence: 99%
“…66 Drugs such as voriconazole and LAMB are used to treat infections caused by Aspergillus species, also other new drugs such as anidulafungin and isavuconazole are considered to be used widespreadly but this requires further studies. 54,67,68 For example, the results of a recent study showed that prophylaxis with isavuconazole is not effective in preventing invasive Aspergillus infections, and further studies are needed to use this drug widely. 52 Furthermore, drug resistance is a critical issue in Aspergillus species.…”
Section: Aspergillosismentioning
confidence: 99%
“…Fluconazole (FLC), a triazole antifungal with fungistatic activity against many Candida species, is one of the most frequently prescribed antifungal drugs (17). It is widely employed prophylactically in high-risk patients and especially in neonates (3,18), is the preferred treatment for Candida osteomyelitis and infections of the eyes and urinary tract (3), and is an appropriate step-down therapy for candidemia, disseminated hepatosplenic candidiasis, and central nervous system and intravascular infections in patients infected with isolates that are unlikely to be fluconazole resistant or are without prior fluconazole exposure (3). CBPs have been developed for fluconazole with several common Candida species (19), and ECVs have been proposed for some less common species (20).…”
mentioning
confidence: 99%
“…The importance of initiating antimycotic therapy against invasive fungal infections as early as possible is repeatedly stressed in the reviews of this Special Issue [1,4,7,10,11]. Consequently, considering the time required for isolation, identification and susceptibility testing, the initial therapy is often empiric.…”
mentioning
confidence: 99%
“…Children/neonates present special challenges, such as the difficulty or impossibility of obtaining information directly from the patient and the need to adapt therapeutic protocols to the anatomy and physiology of this population [11]. Antifungal treatment in pediatric patients often involves prophylaxis in at-risk populations, such as neonates and immunosuppressed patients, or therapeutic intervention for treatment of active mycoses.…”
mentioning
confidence: 99%
See 1 more Smart Citation